2018
DOI: 10.1111/asj.13023
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of a pedometer device for detecting estrus in standing heat and silent heat in Japanese Black cattle

Abstract: The usefulness of a radiotelemetric pedometer for estrus detection in standing (ST) heat, or in silent heat without ST events, but in which ovulation is observed, in Japanese Black cattle was investigated. The duration of an increase in steps in ST heat was 11.8 ± 1.3 hr, and it was similar to that of ST events (duration: 10.1 ± 0.8 hr). Even in silent heat, the change pattern and the duration (11.6 ± 0.2 hr) of the period with an increase in steps during estrus were not different compared with ST heat. When a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
4
1
1
Order By: Relevance
“…Duration of oestrus observed in the present experiment is comparable to the mean duration (13.4 h) reported for cows monitored for oestrus by visual observation of both primary (standing to be mounted) and multiple secondary signs of estrous behavior (Roelofs et al, 2004). Similarly duration of oestrus activity for cows found to be 16.1±4.7h (Accelerometer), 13.0±0.8 h (activity monitoring system) and 14.3±4.1h (Heat time) and 15±4h (Ice tag) respectively but findings here was higher than of , Aungier et al, (2012) and Hojo et al, (2018). Discrepancies between duration of oestrus based on standing events or visual observation with that recorded based on activity are possibly due to the uncoupling of expression of secondary signs of oestrus behaviour and standing oestrus and this could be due to different device being utilized for estrus detection.…”
Section: Relationship Between Increase In Steps and Time Of Ovulationcontrasting
confidence: 42%
See 1 more Smart Citation
“…Duration of oestrus observed in the present experiment is comparable to the mean duration (13.4 h) reported for cows monitored for oestrus by visual observation of both primary (standing to be mounted) and multiple secondary signs of estrous behavior (Roelofs et al, 2004). Similarly duration of oestrus activity for cows found to be 16.1±4.7h (Accelerometer), 13.0±0.8 h (activity monitoring system) and 14.3±4.1h (Heat time) and 15±4h (Ice tag) respectively but findings here was higher than of , Aungier et al, (2012) and Hojo et al, (2018). Discrepancies between duration of oestrus based on standing events or visual observation with that recorded based on activity are possibly due to the uncoupling of expression of secondary signs of oestrus behaviour and standing oestrus and this could be due to different device being utilized for estrus detection.…”
Section: Relationship Between Increase In Steps and Time Of Ovulationcontrasting
confidence: 42%
“…Similarly duration of behavioral oestrus was on average 2hr longer (11.8hr) compared to pedometer oestrus (10.0 hr) . A.I done at 15.5hr and 14.4hr based on standing heat and silent heat measured by radiotelemetric pedometer with conception rate of 57.1% and 60% respectively (Hojo et al, 2018). Further, conception rate was more (90% vs. 58%) when A.I done 10-18hrs after an increase in pedometer activity compared to A.M-P.M rule (Yoshioka et al, 2010).…”
Section: Pedometer Estrus Alert and Timing Of Inseminationmentioning
confidence: 96%
“…Hojo et al . [ 57 ] also reported that activity monitoring using a pedometer-based system can be effectively used for the detection of silent estrus without standing events. Michaelis et al .…”
Section: Strategies For the Treatment Of Estrus And Ovulation Disordersmentioning
confidence: 99%
“…When sensors were used in cattle farms to monitor the activity level (acceleration), step count, and body temperature, estrus was reported to be detected more accurately than by visual observation [ 29 ]. Furthermore, breeding using sensors has been reported to cause no difference in the pregnancy rate of beef cattle with weak signs of estrus [ 30 ]; the estrus detection rate and accuracy and the breeding rate can in fact be improved by the use of sensors. As sensing is also available for health management, sensors are expected to be useful for fertility improvement by promoting not only estrus detection but also health protection of the herd.…”
Section: Reproductive Strategies For the Mitigation Of Global Warmingmentioning
confidence: 99%